Pole force and inertial measurements to analyze cross-country skiing performance in field conditions - Nikkola, A.; Särkkä, O.; Suuriniemi, S.; Kettunen, L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
This study investigates the fusion of pole force measurement, inertial speed measurement, and video analysis to determine cross-country skiing performance in field conditions. As a proof of concept, a preliminary study was performed with different grip designs and double poling technique. The test showed that with exploiting inertial measurements, the average speed could be determined for any number of full cycles or separately for each cycle, which may be difficult with other methods in field conditions. The exploited measurements were appropriate for determining the key characteristics of the double poling cycle, which along with the estimated speed data can be used for comparing skiing economy, determining maximum performance, and finding differences in ski equipment.